Sol : Volume 2 - Hijmans, Steven E. (Brill, 2024)
With this analysis of Sol images, Steven E. Hijmans paints a new picture of the solar cult in ancient Rome. The paucity of literary evidence led Hijmans to prioritize visual sources, and he opens this study with a thorough discussion of the theoretical and methodological issues involved. Emphasizing the danger of facile equivalencies between visual and verbal meanings, his primary focus is Roman praxis, manifest in, for instance, the strict patterning of Sol imagery. These patterns encode core concepts that Sol imagery evoked when deployed, and in those concepts we recognize the bedrock of Rome’s understandings of the sun and his cult. Case studies illustrate these concepts in action and the final chapter analyzes the historical context in which previous, now discredited views on Sol could arise. This is volume II of a two-volume set
10.1163/9789004521582
Keywords: Sun; Idols and images